Total pancreatectomy with islet autotransplantation – a new pain management strategy in chronic pancreatitis? - Chelchowska, Anna; Silva, Michael A. (Journal of the Nuffield Department of Surgical Sciences, 2021)
I haven't attached an abstract, since the author guidelines page says: "An abstract is not required for the surgical case study".